Development of novel device technologies for safer MRI guided biopsy procedures - Uzun, Doğangün. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2023., 2023)
Interventional magnetic resonance imaging (iMRI) is a potent method that combines the benefits of minimally invasive procedures and the exquisite imaging capabilities of MRI. Therefore, performing biopsy operations under the guidance of realtime MR imaging can increase success and safety of operations by promising precise, accurate, and safe MR-guided biopsy operations. Designing visible and safe interventional equipment continues to be a major challenge in this field as MRI develops into a more accessible and suitable imaging modality for interventional procedures. In this thesis study novel device technologies that could improve the success of MR- guided biopsy procedures are introduced and tested. First, a novel optical fiber force sensor was designed and implemented into a needle to provide feedback on the axial force applied to the needle tip during MR-guided biopsy operations. Accurate force measurement, differentiation of different tissue types via stiffness detection capabilities, and the performance of the sensor under MRI were successfully tested through invitro experiments. Next, a novel method for increasing the visibility of MR-compatible interventional devices was introduced by using alternating current (AC) controlled conductive ink printed tracking markers. An elaborate analysis was performed to obtain the highest tracking marker conspicuity using the AC-controlled markers and three commonly used MRI pulse sequences. A Custom 20-gauge needle prototype and an MR-compatible current supply circuit were designed. MR-visibility and safety of the prototypes were tested through in-vitro experiments according to the international medical device test standards. Finally, the performance of the needle prototype and the current supply circuit was tested in a post-mortem animal experiment. NOTE Keywords : Interventional MRI, MR-guided biopsy, Fiber-optic force sensors, iMRI device tracking, AC-controlled markers.
Keywords: Interventional magnetic resonance imaging.; Magnetic resonance imaging.; Biopsy.; Fiber-optic force sensors.